The Importance of Non-Disclosure Agreements in Employment Contracts: Protecting Trade Secrets Beyond the Terms of Standard Employment Contracts: Pentingnya Perjanjian Kerahasiaan dalam Kontrak Kerja: Melindungi Rahasia Dagang Melampaui Ketentuan Kontrak Kerja Standar - Zayyan, Dhaifina; Yudhantaka, Lintang (Faculty of Law Hang Tuah University, 2025)
This study examines the importance of trade secret protection in Indonesia. Trade secret protection is crucial for maintaining honesty and fairness in business competition. Without it, companies can face theft and espionage, which harm the owners of these valuable intangible assets. An NDA is legally binding, meaning that the parties signing the agreement are obligated to comply with all agreed terms. If one party violates the NDA, for example by leaking confidential information, the injured party has the right to seek compensation through legal channels. Law Number 30 of 2000 stipulates criminal sanctions for violations of Article 17 of Trade Secrets or actions that violate Articles 13 or 14, which can be punished with a maximum of two years' imprisonment or a fine of up to Rp 300 million, or through arbitration and alternative dispute resolution methods such as negotiation, mediation, or conciliation, in accordance with Law Number 30 of 1999.